Links of family- and school-level socioeconomic status to academic achievement among Chinese middle school students: A multilevel analysis of a national study. (2020) - Xue, Ye; Xuan, Xin; Zhang, Meixuan; Li, Mian; Jiang, Wen; Wang, Yun
Highlights: Family- and school- level SES positively predict Chinese middle school students' math and Chinese achievement. High school SES facilities students with high family SES achieve high math achievement in rural schools. High school SES facilities students with high or low family SES achieve high academic achievement in urban schools. Abstract: This study examines the unique and interactive relations between family- and school-level socioeconomic status (SES) and Chinese middle school students' math and Chinese achievement. The sample includes 10, 784 middle school students from 199 schools across rural and urban regions. Two-level multilevel analyses suggest that family- and school-level SES are positively related to individual students' math and Chinese achievement. Furthermore, school-level SES strengthens the association between family SES and students' math achievement in rural schools. By contrast, the family SES x school SES interaction is not significant in urban regions. The findings suggest that students from low-SES schools and families in rural China are especially in need of academic support and educational services to close the achievement gap.